Correlation and path coefficient analysis of mango (Mangifera indica L.) - Majumder, DAN; Hassan, L; Rahim, MA; Kabir, MA (Bangladesh Journal of Agricultural Research, 2012)
Sixty diverse genotypes of mango were selected from the Germplasm Centre of BAU during December 2007August 2009 to determine the genotypic and phenotypic correlation along with their direct and indirect effects through path coefficients analysis in mango as to estimate the contribution of most important characters towards yield. It appeared that in most of the cases, the genotypic correlation values were higher than their corresponding phenotypic values. This suggests that there were strong inherent relationship between the traits. Percent flowering shoot had significant positive correlation with inflorescence per shoot, percent perfect flower, percent initial fruit set, number of fruits per plant and fruit weight both at phenotypic and genotypic levels. Fruit yield is determined by some components. The residual effects of genetic and phenotypic path analysis were 0.209 and 0.385, respectively, revealed higher genetic variability and also proved lower percent of environmental influence on the selected ten characters. In genotypic path analysis, number of fruits per plant had the highest positive direct effect (0.899) on yield. Higher positive direct effects were also observed for the characters inflorescence per shoot (0.539), percent perfect flower (0.816), and percent initial fruit set (0.292), and fruit weight (0.324). Leaf area, percent flowering shoot, number of fruits per plant, and fruit length showed negative direct effects towards yield. In phenotypic path analysis, except percent flowering, shoot per plant and fruit length and other characters also exhibited similar trend on yield as genotypic path coefficient. In combination with correlation coefficient and path analysis, it was found that number of fruits per plant and percent perfect flower gave significant positive correlation coefficients with yield and also produce the high positive direct effect. Thus, it was clear that plant height, inflorescence per shoot, percent perfect flower, percent initial fruit set per inflorescence, and fruit weight are the major component of fruit yield in mango. Bangladesh J. Agril. Res. 37(3): 493-503, September 2012 DOI: http://dx.doi.org/10.3329/bjar.v37i3.12126